Coronary Physiology in Patients with Stable and Unstable Coronary Artery Disease - Evaluation of Instantaneous Wave-Free Ratio - Berntorp, Karolina ; 0000-0001-8966-2112 (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2025)
Background: Revascularization of a stenosis is warranted when hemodynamically significant. Coronary physiology provides a diagnostic tool for assessment of stenosis severity to aid in the decision to revascularize or defer. The iFR-SWEDEHEART trial demonstrated non-inferiority of the instantaneous wave-free ratio (iFR) compared to fractional flow reserve (FFR) in guiding decision-making in coronary revascularization, with no difference in major adverse cardiac events (MACE) over the course of one year. The goal of the research reported in this thesis was to characterize the efficacy of iFR-guidance of revascularization in patients varying in clinical presentation. Methods: This thesis comprises five studies. Studies I-III are based on data of the iFR-SWEDEHEART trial, a multicentre randomized clinical trial with 2,037 patients enrolled. Study I was a comparison of costs related to iFR and FFR in the 12 months post-procedure. Study II investigated the five-year rate of prespecified clinical endpoints in the population of the iFR-SWEDEHEART trial. Study III determined rate of MACE in the iFR-SWEDEHEART population with revascularization deferred based on the iFR index compared to FFR, as well as differences in those presenting with stable angina pectoris (SAP) vs. acute coronary syndrome (ACS). Studies IV and V employed data obtained from the nationwide quality registry, SWEDEHEART. Study IV compared MACE rate in patients deferred from revascularization of the left main coronary artery (LMCA) based on intravascular ultrasound (IVUS) to those deferred based on coronary physiology (iFR or FFR). Study V compared deferral rate with iFR to that with FFR in three coronary vessels and determined rate of clinical endpoints of deferred lesions in each vessel over a five-year period. Results: The iFR-guided revascularization was associated with significant cost savings compared to FFR-guided in the first year following the procedure. Long-term follow-up of the iFR-SWEDEHEART population revealed no difference in clinical endpoints in those undergoing iFR vs. FFR. No difference in MACE rate was observed in the long-term follow-up of the deferred population. The outcomes of the deferred population did not differ with clinical presentation of SAP or ACS. There was no difference in rate of the composite endpoint following deferral of LMCA lesions based on coronary physiology indices vs. IVUS, but higher all-cause death was observed in those deferred with IVUS. The deferral rate was higher when using iFR in all investigated vessels, with preserved clinical outcomes. Conclusions: Use of iFR to assess severity of coronary stenosis and guide revascularization is comparable to FFR in safety and effectiveness over the long-term and shows financial benefits over FFR. Wider knowledge of its advantages should lead to its broader adoption in clinical practice.